REPENSAR A MISSÃO DA IGREJA COM OS OLHOS NO REINO DE DEUS: UMA ANÁLISE DO CONCEITO DE REINO DE DEUS NAS TEOLOGIAS LATINO-AMERICANAS DA LIBERTAÇÃO E DA MISSÃO INTEGRAL - Almeida, Roger Alves de (2017)
This work aims to analyze the concepts of the Kingdom of God in the Latin American theologies of the liberation of Gustavo Gutiérrez and the integral mission of René Padilla through a bibliographical research of the authors, as well as possible divergent and convergent questions, identifying the causes Of his writings on the subject, establishing the importance of the concept in relation to the questions of the theology of the mission of the church and demonstrating to what extent his propositions are shown as a continuation of the prevailing theology or rupture. The bibliographical analysis will focus mainly on the texts produced by Gustavo Gutiérrez and René Padilla, especially those that discuss discussions about the kingdom of God and the church in the mission of the church, pointing out the definitions of the Kingdom of God and the repercussions that the relationship between them Plays in the formulation of Latin American theology to identify the issues we will put into dialogue to identify some divergences and convergences. But certainly other authors will appear in dialogue with the research.